PE omnibearing conductive sponge and production process thereof

CN122978520APending Publication Date: 2026-10-27YIYANG FOAMMETAL NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611489089.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-23
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

脱落的金属或底层碎屑还可能进入电子设备内部,造成污染或短路隐患

Benefits of technology

[0024]本发明通过在PE海绵基体与金属镀层之间设置由改性聚氨酯形成的功能基层,实现界面相容、金属锚固与刚韧过渡的协同增强;其中,改性醇单体中的C12-C18长链脂肪烷基与PE分子链具有较好的结构相容性,能够降低功能基层与PE基体之间的界面能,改善功能浸渍液对PE海绵孔壁的润湿和铺展,并通过分子间作用及链段缠结提高功能基层在PE表面的附着稳定性;同时,长链脂肪烷基具有一定的柔性,可随PE海绵压缩和回弹而协调变形,减少PE基体与功能基层界面处的应力集中。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to a kind of PE all-around conductive sponge and its production process, belong to conductive material technical field.The conductive sponge includes the PE sponge matrix with communicating hole and the functional base layer, chemical copper pre-plating layer and copper-nickel surface plating layer attached in turn;Functional base layer is formed by the solidification of functional impregnation fluid containing modified polyurethane dispersion, modified polyurethane is introduced with long-chain fatty alkyl, branched ester-containing structure and diethanolamine derivative nitrogen-containing, oxygen-containing branched chain modified alcohol monomer, long-chain fatty alkyl improves the wetting and adhesion of functional base layer to PE matrix, nitrogen-containing, oxygen-containing structure promotes the coordination anchoring of metal active species, branched ester-containing structure adjusts the rigidity of functional base layer, forms stable rigid transition between PE matrix and metal plating layer;The present application can reduce interlayer debonding, plating layer cracking and powder dropping, and the obtained conductive sponge has good all-around conductivity, electromagnetic shielding property and compression cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of conductive materials technology, specifically relating to a PE omnidirectional conductive sponge and its production process. Background Technology

[0002] All-around conductive foam is a composite material in which a continuous metallic conductive layer is formed on a three-dimensional porous elastic skeleton. It combines buffering, shock absorption, grounding conductivity, and electromagnetic shielding functions, and can be installed between housing seams, display modules, connectors, and other electronic components. Among them, polyethylene (PE) foam has the characteristics of low density, low water absorption, good chemical stability, stable compression support, and low cost, making it suitable for conductive buffer components that require a certain degree of support.

[0003] However, PE molecular chains are nonpolar and have low surface energy. Furthermore, during actual assembly, the sponge undergoes repeated compression, rebound, or lateral shearing, resulting in a significant difference in deformation capacity between the soft porous framework, the polymer underlayer, and the rigid metal layer. Strain tends to concentrate at the interface between the coating and the sponge substrate, gradually leading to interlayer debonding and intralayer microcracks. Cracks crossing the conductive metal network can sever local pathways, causing the remaining pathways to withstand higher current densities. Detached metal or underlayer debris can also enter the electronic equipment, causing contamination or short-circuit hazards. Summary of the Invention

[0004] In order to solve the technical problems mentioned in the background art, the purpose of this invention is to provide a PE omnidirectional conductive sponge and its production process.

[0005] The objective of this invention can be achieved through the following technical solutions:

[0006] A PE omnidirectional conductive sponge includes a PE sponge matrix with interconnected pores, and a functional base layer, a pre-plated layer, and a surface plating layer sequentially attached to the surface; specifically:

[0007] The PE sponge matrix should ideally have a pore density of 55-70 ppi and an open porosity of 95-98% to ensure adequate wetting and coating, and to maintain omnidirectional conductivity.

[0008] The pre-plating layer is preferably a chemically plated copper layer with a thickness of 0.5-0.8 μm, and the surface plating layer preferably includes an electroplated copper layer with a thickness of 6-9 μm and an electroplated nickel layer with a thickness of 0.8-1.2 μm. The copper layer provides a low-resistance continuous network, and the outer nickel layer is used to improve wear resistance and corrosion resistance.

[0009] The functional base layer is formed by curing a functional impregnation liquid, and its components by weight are: 100 parts modified polyurethane dispersion, 5.5-7.2 parts water-dispersed polycarbodiimide, 0.3-0.4 parts wetting agent, 0.15-0.2 parts defoamer, 0.18-0.25 parts thickener and 130-150 parts deionized water.

[0010] The modified polyurethane dispersion is prepared by the following steps:

[0011] Step A1: Mix pentaerythritol triacrylate, triethylamine and anhydrous tetrahydrofuran, cool to 0-5°C under a dry nitrogen atmosphere, slowly add fatty acyl chloride while controlling the temperature not to exceed 10°C, and react at 25-30°C for 4-6 hours after the addition is complete. After the reaction is complete, filter to remove ammonium salt, evaporate tetrahydrofuran, wash and dry to obtain the intermediate.

[0012] Furthermore, the ratio of pentaerythritol triacrylate, fatty acyl chloride, triethylamine, and anhydrous tetrahydrofuran is 0.1 mol: 0.11-0.12 mol: 0.12-0.14 mol: 150-200 mL.

[0013] Preferably, the fatty acid acyl chloride has a fatty chain length of C12-C18.

[0014] Step A2: Premix the intermediate, diethanolamine and anhydrous isopropanol, then add triphenylphosphine and mix. Heat to 55-62℃ under a dry nitrogen atmosphere and react for 8-10 hours. After the reaction is complete, remove the isopropanol by evaporation and then perform thin-film devolatilization to obtain the modified alcohol monomer.

[0015] Furthermore, the ratio of intermediate, diethanolamine, triphenylphosphine and anhydrous isopropanol is 0.1 mol: 0.3 mol: 0.2-0.3 g: 250-330 mL.

[0016] Step A3: Premix polytetrahydrofuran ether diol, 2,2-dimethylolpropionic acid, and anhydrous acetone. Heat the mixture to 60-65°C under a nitrogen atmosphere, add isophorone diisocyanate, and prepolymerize for 2.8-3.5 hours. Then, cool the mixture to 40-50°C and sequentially add dibutyltin dilaurate and modified alcohol monomers for polymerization for 1.5-2 hours. Finally, add 1,4-butanediol for chain extension for 0.5-0.8 hours. After the reaction is complete, evaporate the acetone, add deionized water, and shear disperse to obtain the modified polyurethane dispersion.

[0017] Furthermore, the total NCO / OH equivalent ratio in the preparation of the modified polyurethane dispersion is 1.4-1.6, the NCO / OH equivalent ratio in the prepolymerization reaction is controlled at 2.5-2.8, the hydroxyl molar ratio of polytetrahydrofuran ether diol and 2,2-dimethylolpropionic acid is 1:0.22-0.3; the NCO / OH equivalent ratio in the polymerization reaction is controlled at 1.7-1.9; and dibutyltin dilaurate accounts for 0.03-0.04% of the total amount of reactants.

[0018] A manufacturing process for PE omnidirectional conductive sponge includes the following steps:

[0019] Step S1: The PE sponge matrix is ​​immersed in a nonionic surfactant aqueous solution, then rinsed with deionized water and ethanol aqueous solution in sequence, and dried to obtain a clean sponge matrix.

[0020] Step S2: According to the components of the functional impregnation liquid, premix deionized water, modified polyurethane dispersion, wetting agent and defoamer, then add water-dispersed polycarbodiimide and thickener in sequence and mix well to obtain the functional impregnation liquid. Immerse the clean sponge substrate in the functional impregnation liquid, vacuum impregnate and squeeze out the liquid, dry to form a functional base layer, and obtain the impregnated sponge.

[0021] Step S3: The dip-coated sponge is immersed in palladium activation solution for activation, and then chemical copper plating is used to form a pre-plating layer to obtain the pre-plated sponge;

[0022] Step S4: The pre-plated sponge is electroplated sequentially in copper plating solution and nickel plating solution to form a surface coating containing electroplated copper layer and electroplated nickel layer, thus obtaining PE all-around conductive sponge.

[0023] The beneficial effects of this invention are:

[0024] This invention achieves synergistic enhancement of interfacial compatibility, metal anchoring, and rigid-tough transition by setting a functional base layer formed of modified polyurethane between the PE sponge matrix and the metal coating. The C12-C18 long-chain aliphatic alkyl groups in the modified alcohol monomer have good structural compatibility with the PE molecular chain, reducing the interfacial energy between the functional base layer and the PE matrix, improving the wetting and spreading of the functional impregnation liquid on the PE sponge pore walls, and enhancing the adhesion stability of the functional base layer on the PE surface through intermolecular interactions and chain segment entanglement. Simultaneously, the long-chain aliphatic alkyl groups possess a certain degree of flexibility, allowing for coordinated deformation with the compression and rebound of the PE sponge, reducing stress concentration at the interface between the PE matrix and the functional base layer.

[0025] The modified alcohol monomer, through addition with diethanolamine, introduces multiple nitrogen- and oxygen-containing structures, which, together with ester groups, hydroxyl groups, and urethane groups in the polyurethane, form a multi-site coordination system. This system can coordinate adsorb and locally enrich palladium and copper ions during palladium activation and electroless copper plating, increasing the distribution density and stability of activation centers. Furthermore, it allows the reduced metal to form anchoring points on the surface and near-surface of the functional substrate, thereby enhancing the bonding between the functional substrate and the pre-plating layer. Thus, the long-chain aliphatic alkyl groups primarily strengthen the compatibility and adhesion between the functional substrate and the PE matrix, while the nitrogen- and oxygen-containing structures primarily strengthen the coordination anchoring between the functional substrate and the metal plating layer. These two components act on the inner and outer sides of the functional substrate, respectively, and form a stable interfacial bonding system through a continuous polyurethane network, preventing either interface from becoming a weak point in the composite structure.

[0026] Furthermore, the modified alcohol monomer possesses a multi-armed branched ester-containing structure. Its multiple hydroxyl groups react with isocyanates to form branched crosslinking nodes, which can improve the crosslinking density, cohesive strength, and rigidity of the functional substrate, enabling it to provide stable support for the outer metal plating. The ester groups, hydroxyethyl derivative segments, and long-chain aliphatic alkyl groups in the branches retain appropriate chain mobility, allowing them to disperse and dissipate compressive stress through molecular chain movement and interactions between polar groups, preventing the functional substrate from becoming embrittled due to excessive stiffness. Therefore, the stiffening effect of branched crosslinking and the toughening effect of the flexible ester-containing branches work together to form a moderately stiff and tough transition layer between the soft PE sponge and the rigid copper / nickel plating, reducing the rigidity gradient and deformation differences between adjacent layers.

[0027] Furthermore, the functional base layer forms a synergistic mechanism of "matrix wetting and adhesion - coating coordination and anchoring - interlayer gradient force transmission", which enables external loads to be transmitted and dispersed step by step between the PE matrix, functional base layer and metal coating. This suppresses interlayer debonding, coating cracking and metal powdering caused by repeated compression, maintains the continuity of the three-dimensional conductive network, and ultimately makes the resulting PE all-around conductive sponge have high interlayer bonding strength, stable all-around conductivity, electromagnetic shielding performance and good compression cycle durability. Detailed Implementation

[0028] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0029] Example 1: Preparation of PE omnidirectional conductive sponge, including the following implementation steps:

[0030] I. Preparation of Modified Polyurethane Dispersion

[0031] Step A1: Take 29.8g of pentaerythritol triacrylate (0.1mol) and add triethylamine and anhydrous tetrahydrofuran. Stir and mix, purge with dry nitrogen for 5min, cool to 2℃ using an ice-water bath, slowly add dodecyl chloride while monitoring the liquid temperature to not exceed 10℃, and maintain the temperature at 25℃ for 4h after addition. The ratio of pentaerythritol triacrylate, dodecyl chloride, triethylamine and anhydrous tetrahydrofuran is 0.1mol:0.11mol:0.12mol:150mL. After the reaction is complete, filter to remove ammonium salt. After filtration, remove tetrahydrofuran by rotary evaporation at 42℃ and 8kPa. Wash twice with 100mL of 0.5% sodium bicarbonate aqueous solution and once with 100mL of saturated sodium chloride aqueous solution and separate the aqueous phase. Dry the organic phase with 20g of anhydrous sodium sulfate for 30min and filter to obtain the intermediate.

[0032] Step A2: Take 38.5g of intermediate (measured as 0.08mol) and add diethanolamine and anhydrous isopropanol. Stir and premix, then add triphenylphosphine and stir to mix. Purge with dry nitrogen for 5min and heat to 55℃ for 8h. The ratio of intermediate, diethanolamine, triphenylphosphine and anhydrous isopropanol is 0.1mol:0.3mol:0.2g:250mL. After the reaction is complete, remove isopropanol by rotary evaporation at 50℃ and 8kPa, and then perform two thin-film devolatilizations at 90℃ and 0.4kPa to obtain the modified alcohol monomer.

[0033] Step A3: Using 111.2 g of isophorone diisocyanate (measured as 0.5 mol) as the isocyanate raw material, polytetrahydrofuran ether diol (molecular weight 1000, hydroxyl value 110 mg KOH / g) as the diol raw material, 2,2-dimethylolpropionic acid as the hydrophilic raw material, and modified alcohol monomer as the modifying raw material; the modified polyurethane is synthesized in three continuous steps: prepolymerization, polymerization, and chain extension. In the prepolymerization reaction, the raw material calculation is controlled according to an NCO / OH equivalent ratio of 2.5, and the hydroxyl molar ratio of polytetrahydrofuran ether diol and 2,2-dimethylolpropionic acid is 1:0.22. In the polymerization reaction, the NCO / OH equivalent ratio is controlled at 1.7, and the total NCO / OH equivalent ratio is controlled at 1.4 for 1,4-butanediol chain extension. The specific synthesis process is as follows:

[0034] Polytetrahydrofuran ether diol and 2,2-dimethylolpropionic acid were added and premixed with 200 mL of anhydrous acetone. Nitrogen gas was introduced for 10 min, and the temperature was raised to 60 °C. Isophorone diisocyanate was slowly added over 30 min, and stirring was continued after addition for prepolymerization reaction, which lasted for 2.8 h. The temperature was then lowered to 40 °C, and 0.03% of dibutyltin dilaurate and modified alcohol monomer were added sequentially. The polymerization reaction was stirred for 1.5 h. Finally, 1,4-butanediol was added for chain extension reaction for 0.8 h. After the reaction was completed, acetone was removed at 45 °C and 10 kPa. Deionized water was added at a solid content of 35%, and the mixture was sheared at 1200 rpm for 10 min to prepare a modified polyurethane dispersion.

[0035] II. Preparation of Functional Impregnation Solution

[0036] 100 parts of modified polyurethane dispersion; 5.5 parts of water-dispersed polycarbodiimide with a solid content of 40% and a carbodiimide equivalent of 350 g / eq; 0.3 parts of wetting agent (BETTERSOL 607 type acetylenic diol wetting agent); 0.15 parts of defoamer (BYK-057 type silicone-free defoamer); 0.18 parts of thickener (RHEOBYK-7600 nonionic polyurethane associative thickener); 130 parts of deionized water; 1 part of each component is 2 g.

[0037] Deionized water, modified polyurethane dispersion, wetting agent and defoamer were added and premixed at 300 rpm for 10 min. Then the speed was reduced to 120 rpm, and water-dispersed polycarbodiimide and thickener were added sequentially and mixed for 15 min to obtain functional impregnation liquid.

[0038] III. Preparation of PE All-Around Conductive Sponge

[0039] Step S1: Select PE sponge with specifications of 200×200mm×5mm, pore density of 60ppi, and open porosity of 96.5%; immerse the PE sponge matrix in 2% nonionic surfactant aqueous solution for 5min, then immerse it in deionized water and 30% ethanol aqueous solution for 30min in sequence, squeeze dry and dry at 50℃ to obtain clean sponge matrix.

[0040] Step S2: Immerse the clean sponge substrate in the functional impregnation liquid, maintain an absolute pressure of 15 kPa for 3 minutes, restore normal pressure after 45 seconds, compress the sponge to 40% of its original thickness and squeeze out the liquid, repeat the vacuum impregnation and squeezing process once, so that a total of 2 impregnations are completed, and dry the sample at 60℃ for 20 minutes to obtain the impregnated sponge.

[0041] Step S3: The dip-coated sponge is treated in an activation solution at 30℃ for 5 minutes. The activation solution contains 0.15 g / L palladium chloride, 10 g / L sodium chloride, and 1.5 mL / L hydrochloric acid with a mass fraction of 37%. After rinsing with water, it is reduced in a 0.5 g / L sodium borohydride solution at 23℃ for 1 minute. Then, it is treated in a chemical copper plating solution at 32℃ and pH 12.5 for 8 minutes. The plating solution contains 12 g / L copper sulfate pentahydrate, 25 g / L disodium ethylenediaminetetraacetate, 12 g / L potassium sodium tartrate, and 8 mL / L formaldehyde aqueous solution with a mass fraction of 37%. A copper plating layer with a thickness of about 0.55 μm is formed, and the pre-plated sponge is obtained.

[0042] Step S4: The pre-plated sponge is placed in a copper plating solution containing 190 g / L copper sulfate pentahydrate, 50 g / L sulfuric acid, and 60 mg / L chloride ions, and first at 25°C with a flux of 0.25 A / dm 2 Power on for 3 minutes, then apply 0.80 A / dm 2 Electroplating for 35 min yielded a copper layer with a thickness of 6.5 μm; after rinsing with water, it was then plated in a nickel plating solution containing 240 g / L nickel sulfate hexahydrate, 45 g / L nickel chloride hexahydrate, and 35 g / L boric acid at 50 °C, pH 4.2, and 0.50 A / dm³. 2 Electroplating for 6 minutes yields a nickel plating layer with a thickness of 0.8 μm; the copper plating layer and the nickel plating layer together form the surface coating, resulting in a PE omnidirectional conductive sponge.

[0043] Example 2, preparation of PE omnidirectional conductive sponge, including the following implementation:

[0044] I. Preparation of Modified Polyurethane Dispersion

[0045] Step A1: Take 29.8g of pentaerythritol triacrylate (0.1mol) and add triethylamine and anhydrous tetrahydrofuran. Stir and mix, purge with dry nitrogen for 5min, cool to 5℃ using an ice-water bath, slowly add hexadecyl chloride while monitoring the liquid temperature to not exceed 10℃, and maintain the temperature at 28℃ for 5h after addition. The ratio of pentaerythritol triacrylate, hexadecyl chloride, triethylamine and anhydrous tetrahydrofuran is 0.1mol:0.11mol:0.13mol:170mL. After the reaction is complete, filter to remove ammonium salt. After filtration, remove tetrahydrofuran by rotary evaporation at 42℃ and 8kPa. Wash twice with 100mL of 0.5% sodium bicarbonate aqueous solution and once with 100mL of saturated sodium chloride aqueous solution and separate the aqueous phase. Dry the organic phase with 20g of anhydrous sodium sulfate for 30min and filter to obtain the intermediate.

[0046] Step A2: Take 42.9g of intermediate (measured as 0.08mol) and add diethanolamine and anhydrous isopropanol. Stir and premix, then add triphenylphosphine and stir to mix. Purge with dry nitrogen for 5min and heat to 60℃ for 9.5h. The ratio of intermediate, diethanolamine, triphenylphosphine and anhydrous isopropanol is 0.1mol:0.3mol:0.3g:300mL. After the reaction is complete, remove isopropanol by rotary evaporation at 50℃ and 8kPa, and then perform two thin-film devolatilizations at 90℃ and 0.4kPa to obtain the modified alcohol monomer.

[0047] Step A3: Using 111.2 g of isophorone diisocyanate (measured as 0.5 mol) as the isocyanate raw material, polytetrahydrofuran ether diol (molecular weight 1000, hydroxyl value 110 mg KOH / g) as the diol raw material, 2,2-dimethylolpropionic acid as the hydrophilic raw material, and modified alcohol monomer as the modifying raw material; the modified polyurethane is synthesized in three continuous steps: prepolymerization, polymerization, and chain extension. In the prepolymerization reaction, the raw material calculation is controlled according to an NCO / OH equivalent ratio of 2.6, and the hydroxyl molar ratio of polytetrahydrofuran ether diol and 2,2-dimethylolpropionic acid is 1:0.25. In the polymerization reaction, the NCO / OH equivalent ratio is controlled at 1.8, and the total NCO / OH equivalent ratio is controlled at 1.5 for 1,4-butanediol chain extension. The specific synthesis process is as follows:

[0048] Polytetrahydrofuran ether diol and 2,2-dimethylolpropionic acid were added and premixed with 250 mL of anhydrous acetone. Nitrogen gas was introduced for 10 min, and the temperature was raised to 65 °C. Isophorone diisocyanate was slowly added over 40 min, and stirring was continued for prepolymerization for 3.2 h. The temperature was then lowered to 50 °C, and 0.04% of the total reactants, dibutyltin dilaurate and modified alcohol monomer were added sequentially. The polymerization reaction was stirred for 1.7 h. Finally, 1,4-butanediol was added for chain extension for 0.6 h. After the reaction was completed, acetone was removed at 45 °C and 10 kPa. Deionized water was added at a solid content of 35%, and the mixture was sheared at 1200 rpm for 10 min to prepare a modified polyurethane dispersion.

[0049] II. Preparation of Functional Impregnation Solution

[0050] The following components were included: 100 parts of modified polyurethane dispersion; 6.8 parts of water-dispersed polycarbodiimide with a solid content of 40% and a carbodiimide equivalent of 350 g / eq; 0.4 parts of wetting agent (BETTERSOL 607 type acetylenic diol wetting agent); 0.17 parts of defoamer (BYK-057 type silicone-free defoamer); 0.22 parts of thickener (RHEOBYK-7600 nonionic polyurethane associative thickener); and 145 parts of deionized water.

[0051] Deionized water, modified polyurethane dispersion, wetting agent and defoamer were added and premixed at 300 rpm for 10 min. Then the speed was reduced to 120 rpm, and water-dispersed polycarbodiimide and thickener were added sequentially and mixed for 15 min to obtain functional impregnation liquid.

[0052] III. Preparation of PE All-Around Conductive Sponge

[0053] Step S1: Select PE sponge with specifications of 200×200mm×5mm, pore density of 60ppi, and open porosity of 96.5%; immerse the PE sponge matrix in 2% nonionic surfactant aqueous solution for 5min, then immerse it in deionized water and 30% ethanol aqueous solution for 30min in sequence, squeeze dry and dry at 50℃ to obtain clean sponge matrix.

[0054] Step S2: Immerse the clean sponge substrate in the functional impregnation liquid, maintain an absolute pressure of 15 kPa for 3 minutes, restore normal pressure after 45 seconds, compress the sponge to 40% of its original thickness and squeeze out the liquid, repeat the vacuum impregnation and squeezing process once, so that a total of 2 impregnations are completed, and dry the sample at 60℃ for 20 minutes to obtain the impregnated sponge.

[0055] Step S3: The dip-coated sponge is treated in an activation solution at 30℃ for 5 minutes. The activation solution contains 0.15 g / L palladium chloride, 10 g / L sodium chloride, and 1.5 mL / L hydrochloric acid with a mass fraction of 37%. After rinsing with water, it is reduced in a 0.5 g / L sodium borohydride solution at 23℃ for 1 minute. Then, it is treated in a chemical copper plating solution at 32℃ and pH 12.5 for 12 minutes. The plating solution contains 12 g / L copper sulfate pentahydrate, 25 g / L disodium ethylenediaminetetraacetate, 12 g / L potassium sodium tartrate, and 8 mL / L formaldehyde aqueous solution with a mass fraction of 37%. A copper plating layer with a thickness of about 0.65 μm is formed, and the pre-plated sponge is obtained.

[0056] Step S4: The pre-plated sponge is placed in a copper plating solution containing 190 g / L copper sulfate pentahydrate, 50 g / L sulfuric acid, and 60 mg / L chloride ions, and first at 25°C with a flux of 0.25 A / dm 2 Power on for 3 minutes, then apply 0.80 A / dm 2 Electroplating for 40 min yielded a copper layer with a thickness of 7.8 μm; after rinsing with water, it was then plated in a nickel plating solution containing 240 g / L nickel sulfate hexahydrate, 45 g / L nickel chloride hexahydrate, and 35 g / L boric acid at 50 °C, pH 4.2, and 0.50 A / dm³. 2 Electroplating for 9 minutes yields a nickel plating layer with a thickness of 1.1 μm; the copper plating layer and the nickel plating layer together form the surface plating layer, resulting in a PE omnidirectional conductive sponge.

[0057] Example 3, preparation of PE omnidirectional conductive sponge, including the following implementation:

[0058] I. Preparation of Modified Polyurethane Dispersion

[0059] Step A1: Take 29.8g of pentaerythritol triacrylate (0.1mol) and add triethylamine and anhydrous tetrahydrofuran. Stir and mix, purge with dry nitrogen for 5min, cool to 0℃ using an ice-water bath, slowly add octadecyl chloride while monitoring the liquid temperature to not exceed 10℃, and maintain the temperature at 30℃ for 6h after addition. The ratio of pentaerythritol triacrylate, octadecyl chloride, triethylamine and anhydrous tetrahydrofuran is 0.1mol:0.12mol:0.14mol:200mL. After the reaction is complete, filter to remove ammonium salt. After filtration, remove tetrahydrofuran by rotary evaporation at 42℃ and 8kPa. Wash twice with 100mL of 0.5% sodium bicarbonate aqueous solution and once with 100mL of saturated sodium chloride aqueous solution and separate the aqueous phase. Dry the organic phase with 20g of anhydrous sodium sulfate for 30min and filter to obtain the intermediate.

[0060] Step A2: Take 45.2g of intermediate (measured as 0.08mol) and add diethanolamine and anhydrous isopropanol. Stir and premix, then add triphenylphosphine and stir to mix. Purge with dry nitrogen for 5min and heat to 62℃ for 10h. The ratio of intermediate, diethanolamine, triphenylphosphine and anhydrous isopropanol is 0.1mol:0.3mol:0.3g:330mL. After the reaction is complete, remove isopropanol by rotary evaporation at 50℃ and 8kPa, and then perform two thin-film devolatilizations at 90℃ and 0.4kPa to obtain the modified alcohol monomer.

[0061] Step A3: Using 111.2 g of isophorone diisocyanate (measured as 0.5 mol) as the isocyanate raw material, polytetrahydrofuran ether diol (molecular weight 1000, hydroxyl value 110 mg KOH / g) as the diol raw material, 2,2-dimethylolpropionic acid as the hydrophilic raw material, and modified alcohol monomer as the modifying raw material; the modified polyurethane is synthesized in three continuous steps: prepolymerization, polymerization, and chain extension. In the prepolymerization reaction, the raw material calculation is controlled according to an NCO / OH equivalent ratio of 2.8, and the hydroxyl molar ratio of polytetrahydrofuran ether diol and 2,2-dimethylolpropionic acid is 1:0.3. In the polymerization reaction, the NCO / OH equivalent ratio is controlled at 1.9, and the total NCO / OH equivalent ratio is controlled at 1.6 for 1,4-butanediol chain extension. The specific synthesis process is as follows:

[0062] Polytetrahydrofuran ether diol and 2,2-dimethylolpropionic acid were added and premixed with 280 mL of anhydrous acetone. Nitrogen gas was introduced for 10 min, and the temperature was raised to 65 °C. Isophorone diisocyanate was slowly added over 45 min, and stirring was continued for prepolymerization for 3.5 h. The temperature was then lowered to 50 °C, and 0.04% of the total reactants, dibutyltin dilaurate and modified alcohol monomer were added sequentially. The polymerization reaction was stirred for 2 h. Finally, 1,4-butanediol was added for chain extension for 0.5 h. After the reaction was completed, acetone was removed at 45 °C and 10 kPa. Deionized water was added at a solid content of 35%, and the mixture was sheared at 1200 rpm for 10 min to prepare a modified polyurethane dispersion.

[0063] II. Preparation of Functional Impregnation Solution

[0064] The following components were included: 100 parts modified polyurethane dispersion; 7.2 parts water-dispersed polycarbodiimide with a solid content of 40% and a carbodiimide equivalent of 350 g / eq; 0.4 parts wetting agent (BETTERSOL 607 type acetylenic diol wetting agent); 0.2 parts defoamer (BYK-057 type silicone-free defoamer); 0.25 parts thickener (RHEOBYK-7600 nonionic polyurethane associative thickener); and 150 parts deionized water.

[0065] Deionized water, modified polyurethane dispersion, wetting agent and defoamer were added and premixed at 300 rpm for 10 min. Then the speed was reduced to 120 rpm, and water-dispersed polycarbodiimide and thickener were added sequentially and mixed for 15 min to obtain functional impregnation liquid.

[0066] III. Preparation of PE All-Around Conductive Sponge

[0067] Step S1: Select PE sponge with specifications of 200×200mm×5mm, pore density of 60ppi, and open porosity of 96.5%; immerse the PE sponge matrix in 2% nonionic surfactant aqueous solution for 5min, then immerse it in deionized water and 30% ethanol aqueous solution for 30min in sequence, squeeze dry and dry at 50℃ to obtain clean sponge matrix.

[0068] Step S2: Immerse the clean sponge substrate in the functional impregnation liquid, maintain an absolute pressure of 15 kPa for 3 minutes, restore normal pressure after 45 seconds, compress the sponge to 40% of its original thickness and squeeze out the liquid, repeat the vacuum impregnation and squeezing process once, so that a total of 2 impregnations are completed, and dry the sample at 60℃ for 20 minutes to obtain the impregnated sponge.

[0069] Step S3: The dip-coated sponge is treated in an activation solution at 30℃ for 5 minutes. The activation solution contains 0.15 g / L palladium chloride, 10 g / L sodium chloride, and 1.5 mL / L hydrochloric acid with a mass fraction of 37%. After rinsing with water, it is reduced in a 0.5 g / L sodium borohydride solution at 23℃ for 1 minute. Then, it is treated in a chemical copper plating solution at 32℃ and pH 12.5 for 14 minutes. The plating solution contains 12 g / L copper sulfate pentahydrate, 25 g / L disodium ethylenediaminetetraacetate, 12 g / L potassium sodium tartrate, and 8 mL / L formaldehyde aqueous solution with a mass fraction of 37%. A copper plating layer with a thickness of about 0.72 μm is formed, and the pre-plated sponge is obtained.

[0070] Step S4: The pre-plated sponge is placed in a copper plating solution containing 190 g / L copper sulfate pentahydrate, 50 g / L sulfuric acid, and 60 mg / L chloride ions, and first at 25°C with a flux of 0.25 A / dm 2 Power on for 5 minutes, then apply 0.80 A / dm 2 Electroplating for 45 min yielded a copper plating layer with a thickness of 8.5 μm; after rinsing with water, it was then plated in a nickel plating solution containing 240 g / L nickel sulfate hexahydrate, 45 g / L nickel chloride hexahydrate, and 35 g / L boric acid at 50 °C, pH 4.2, and 0.50 A / dm³. 2 Electroplating for 10 minutes yields a 1.2 μm thick nickel plating layer; the copper plating layer and the nickel plating layer together form the surface coating, resulting in a PE omnidirectional conductive sponge.

[0071] Comparative Example 1, following the implementation method of Example 3, in the preparation of the modified polyurethane dispersion, NJ-6305B type sorbitol-based polyether polyol was used to replace the modified alcohol monomer in equal amounts according to the hydroxyl content, and the rest of the implementation method was the same.

[0072] Comparative Example 2, referring to the implementation method of Example 3, in the process of preparing the functional impregnation liquid, PU-1008 type waterborne polyurethane dispersion was used to replace the modified polyurethane dispersion in an equal amount according to the isocyanate group content, and the rest of the implementation method was the same.

[0073] The intermediate obtained in Example 3 was subjected to 1H NMR, 1C NMR, and infrared spectroscopy. The key detection data are as follows:

[0074] 1 In the 1H NMR spectrum, proton signals of acrylate double bonds appeared at δ6.43, 6.13 and 5.84 ppm, corresponding to a total of 9H; two types of OCH2 proton signals in the pentaerythritol skeleton appeared at δ4.32 and 4.17 ppm, respectively; and characteristic proton signals of the octadecyl group long chain appeared at δ2.33, 1.62, 1.26 and 0.88 ppm.

[0075] 13In the CNMR spectrum, carbonyl carbon signals of octadecyl ester and acrylate appeared at δ173.5 and 165.7 ppm, respectively; carbon signals of acrylate double bond appeared at δ131.4 and 128.2 ppm; and carbon signals of long-chain methylene appeared at δ29.1-29.7 ppm.

[0076] In the FT-IR spectrum, 1736-1722 cm⁻¹ -1 Ester carbonyl absorption appears at 1636, 985 and 810 cm⁻¹. -1 The characteristic absorption of acrylate double bonds is retained at 2920, 2850 and 720 cm⁻¹. -1 The characteristic absorption of the octadecyl group long chain was observed, while no obvious broad peak of hydroxyl group was seen. These results indicate that the hydroxyl group in pentaerythritol triacrylate has undergone esterification with octadecyl chloride, retaining three acrylate double bonds, indicating that the target intermediate has been formed.

[0077] The modified alcohol monomer obtained in Example 3 was subjected to 1H NMR, 1C NMR, and infrared spectroscopy. The key detection data are as follows:

[0078] 1 In the 1H NMR spectrum, the proton signal of the acrylate double bond in the original intermediate disappeared in the range of 5.84-6.43 ppm, while the β-amino ester structure and N-CH2 related proton signal appeared near 2.73, 2.63 and 2.45 ppm, the CH2OH proton signal appeared at 3.56 ppm, and the broad peak of alcohol hydroxyl group appeared in the range of 4.2-5.0 ppm.

[0079] 13 In the C NMR spectrum, the double bond carbon signal of acrylate disappeared in the range of 127.5 to 132.0 ppm, the carbonyl carbon signal of β-amino ester appeared at 171.8 ppm, and the carbon signals of CH2N, NCH2CH2OH and CH2OH appeared at 50.6, 56.2 and 59.4 ppm, respectively.

[0080] In the FT-IR spectrum, 3200-3500 cm⁻¹ -1 A distinct broad absorption of hydroxyl groups was observed at 1730 cm⁻¹. -1 The ester carbonyl group retains absorption at 1270-1030 cm⁻¹. -1 CO and CN absorption occurred at 1635, 985, and 810 cm⁻¹. -1 The absorption of the nearby acrylate double bonds disappeared. The above changes indicate that all three acrylate double bonds in the intermediate underwent addition reactions with the secondary amino group of diethanolamine, forming a branched structure containing multiple terminal alcohol hydroxyl groups, indicating that the target modified alcohol monomer has been formed.

[0081] A 100mm×25mm×1mm PE sheet was used as a test sample. The surface was coated with the functional impregnation solution prepared above, dried at 60℃ for 10 min, cured at 80℃ for 30 min, and placed at 23℃ and 50%RH for 48 h. After bonding a PET backing, it was peeled at 100mm / min at 180° to test the peel force of PE / functional base layer. Similarly, the functional impregnation solution was cast and cured according to the above method to form a 0.30±0.02mm free film. The peel force of the functional base layer / coating was tested using the same method according to the corresponding active, chemical plating, and electroplating processes in the implementation process. Specific test results are shown in Table 1.

[0082] Table 1. Interfacial peel force (N / 25mm)

[0083]

[0084] As can be seen from the test results in Table 1, the functional base layer of the embodiment has better adhesion to the PE substrate and the coating than the comparative example.

[0085] Samples were taken from four stages: PE sponge matrix formation, functional base layer formation, pre-coating formation, and surface coating completion. 20mm × 20mm × 20mm cube samples were cut and compressed at 10mm / min. The secant compression modulus was calculated based on the 10-25% strain range to evaluate the stiffness gradient of the sponge at each stage. Specific test results are shown in Table 2.

[0086] Table 2. 10-25% secant compression modulus at different lamination stages / kPa

[0087]

[0088] As can be seen from the test results in Table 2, compared with the comparative example, the rigidity gradient of each layer after attachment is relatively uniform in the embodiment. There is no obvious situation where the soft substrate directly jumps to the complete metal layer. The rigidity of the functional layer in the comparative example 1 is too fast, and the rigidity of the functional base layer in the comparative example 2 is insufficient.

[0089] A 20mm × 20mm × 20mm cubic sample of PE omnidirectional conductive sponge was cut. Gold-plated copper electrodes were placed on two opposite faces in the X, Y, or Z directions. The sample was pre-compressed by 5% and its resistance was measured using a 100mA DC current and a four-wire method. An independent sample was used for each direction, subjected to 30% compressive strain and 20,000 cycles at 1Hz in that direction. After a 30-minute rest period, the resistance was measured again in the same direction. The maximum rate of change was taken as the largest among the X, Y, and Z directions. Specific test results are shown in Tables 3 and 4.

[0090] Table 3 Resistance in each direction before cycling

[0091]

[0092] Table 4. Resistance in each direction after 20,000 cycles

[0093]

[0094] As can be seen from the test results in Tables 3 and 4, the anisotropy ratio of each embodiment before cycling is no higher than 1.12, indicating that vacuum impregnation and continuous pre-plating can establish a uniform conductive network in three directions; after 20,000 cycles, the maximum rate of change of resistance is significantly lower than that of the comparative example, indicating that the stability between the layers on the PE sponge surface is good.

[0095] The average shielding effectiveness under 50% compression was measured in the range of 30MHz-1.5GHz using the coaxial method of ASTM D4935; the shielding effectiveness after cycling was tested after 20,000 compressions in the Z-axis.

[0096] The amount of powder shed was determined after the cycle was completed: a 100mm × 100mm sample was placed in a clean, sealed polyethylene bottle and rolled at 60 rpm for 30 min. The shed particles were collected through a 0.45μm filter membrane, dried at 60℃, weighed, and converted to mg / 100cm³. 2 .

[0097] The specific test results are shown in Table 5:

[0098] Table 5. Shielding and powder loss test results

[0099]

[0100] As can be seen from the test data in Table 5, the PE omnidirectional conductive sponge prepared in the example has high initial shielding effectiveness, low powder shedding, and good compression cycle stability.

[0101] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

Claims

1. A PE omnidirectional conductive sponge, comprising at least a PE sponge matrix, and a functional base layer, a pre-plating layer, and a surface plating layer sequentially attached to the surface, characterized in that, The functional base layer is cured by functional impregnation liquid, and its components by weight are: 100 parts modified polyurethane dispersion, 5.5-7.2 parts water-dispersed polycarbodiimide, 0.3-0.4 parts wetting agent, 0.15-0.2 parts defoamer, 0.18-0.25 parts thickener and 130-150 parts deionized water; The modified polyurethane dispersion is prepared by the following steps: Step A1: Mix pentaerythritol triacrylate, triethylamine and anhydrous tetrahydrofuran, cool to 0-5°C under a dry nitrogen atmosphere, slowly add fatty acyl chloride while controlling the temperature not to exceed 10°C, and react at 25-30°C for 4-6 hours after the addition is complete to prepare the intermediate. Step A2: Premix the intermediate, diethanolamine and anhydrous isopropanol, then add triphenylphosphine and mix. Heat to 55-62℃ under a dry nitrogen atmosphere and react for 8-10 hours to prepare the modified alcohol monomer. Step A3: Premix polytetrahydrofuran ether diol, 2,2-dimethylolpropionic acid and anhydrous acetone, heat to 60-65℃ under a nitrogen atmosphere, add isophorone diisocyanate for prepolymerization reaction for 2.8-3.5h, then cool to 40-50℃ and add dibutyltin dilaurate and modified alcohol monomer sequentially for polymerization reaction for 1.5-2h, finally add 1,4-butanediol for chain extension reaction for 0.5-0.8h to prepare modified polyurethane dispersion.

2. The PE omnidirectional conductive sponge according to claim 1, characterized in that, The ratio of pentaerythritol triacrylate, fatty acyl chloride, triethylamine and anhydrous tetrahydrofuran is 0.1 mol: 0.11-0.12 mol: 0.12-0.14 mol: 150-200 mL.

3. The PE omnidirectional conductive sponge according to claim 2, characterized in that, The fatty chain length of fatty acyl chlorides is C12-C18.

4. The PE omnidirectional conductive sponge according to claim 2, characterized in that, The ratio of intermediate, diethanolamine, triphenylphosphine and anhydrous isopropanol is 0.1 mol: 0.3 mol: 0.2-0.3 g: 250-330 mL.

5. The PE omnidirectional conductive sponge according to claim 4, characterized in that, The total NCO / OH equivalent ratio in the preparation of modified polyurethane dispersion is 1.4-1.6; the NCO / OH equivalent ratio in the prepolymerization reaction is controlled at 2.5-2.8; the hydroxyl molar ratio of polytetrahydrofuran ether diol and 2,2-dimethylolpropionic acid is 1:0.22-0.3; the NCO / OH equivalent ratio in the polymerization reaction is controlled at 1.7-1.9; and dibutyltin dilaurate accounts for 0.03-0.04% of the total amount of reactants.

6. The production process of a PE omnidirectional conductive sponge according to any one of claims 1-5, characterized in that, The process includes the following steps: Step S1: The PE sponge matrix is ​​immersed in a nonionic surfactant aqueous solution, then rinsed with deionized water and ethanol aqueous solution in sequence, and dried to obtain a clean sponge matrix. Step S2: According to the components of the functional impregnation liquid, premix deionized water, modified polyurethane dispersion, wetting agent and defoamer, then add water-dispersed polycarbodiimide and thickener in sequence and mix well to obtain the functional impregnation liquid. Immerse the clean sponge substrate in the functional impregnation liquid, vacuum impregnate and squeeze out the liquid, dry to form a functional base layer, and obtain the impregnated sponge. Step S3: The dip-coated sponge is immersed in palladium activation solution for activation, and then chemical copper plating is used to form a pre-plating layer to obtain the pre-plated sponge; Step S4: The pre-plated sponge is electroplated sequentially in copper plating solution and nickel plating solution to form a surface coating containing electroplated copper layer and electroplated nickel layer, thus obtaining PE all-around conductive sponge.

7. The production process of a PE omnidirectional conductive sponge according to claim 6, characterized in that, The PE sponge matrix has a pore density of 55-70 ppi and an open porosity of 95-98%.

8. The production process of a PE omnidirectional conductive sponge according to claim 6, characterized in that, The pre-plating layer is a 0.5-0.8μm thick electroless copper plating layer, and the surface plating layer is a 6-9μm thick electroplated copper plating layer and a 0.8-1.2μm thick electroplated nickel plating layer.